2018
DOI: 10.1103/physrevlett.121.061802
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Stars Exclude Light Dark Baryons

Abstract: Exotic particles carrying baryon number and with a mass of the order of the nucleon mass have been proposed for various reasons including baryogenesis, dark matter, mirror worlds, and the neutron lifetime puzzle. We show that the existence of neutron stars with a mass greater than 0.7  M_{⊙} places severe constraints on such particles, requiring them to be heavier than 1.2 GeV or to have strongly repulsive self-interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
118
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 36 publications
0
118
0
Order By: Relevance
“…In order to reproduce the observed value of Y B ∼ 8.7 × 10 −11 , the experimental observables in Eq. (2.4) must, after scanning over the (m Φ , Γ Φ ) parameter space, lie within the ranges we conclude that the amount of CP violation predicted by the SM is typically not enough for successful 6 The authors of [40] showed that the observation of neutron stars with masses greater than 2M constrains the mass of a dark particle carrying baryon number to be greater than the neutron chemical potential inside the star, which is about 1.2 GeV. Otherwise, if a light dark baryon did exist, a process such as n + n → DM + DM could occur within the star.…”
Section: Baryogenesis and Dark Matter From B Mesonsmentioning
confidence: 62%
See 1 more Smart Citation
“…In order to reproduce the observed value of Y B ∼ 8.7 × 10 −11 , the experimental observables in Eq. (2.4) must, after scanning over the (m Φ , Γ Φ ) parameter space, lie within the ranges we conclude that the amount of CP violation predicted by the SM is typically not enough for successful 6 The authors of [40] showed that the observation of neutron stars with masses greater than 2M constrains the mass of a dark particle carrying baryon number to be greater than the neutron chemical potential inside the star, which is about 1.2 GeV. Otherwise, if a light dark baryon did exist, a process such as n + n → DM + DM could occur within the star.…”
Section: Baryogenesis and Dark Matter From B Mesonsmentioning
confidence: 62%
“…As an example of an application, in Sec. 2 we have used the results of [40] to restrict our parameter space to dark baryon masses greater than ∼ 1.2 GeV, as lighter dark baryons would lead to a process that would deplete the neutrons (and therefore the Fermi pressure) via conversion into DM within the star. We now examine constraints on our model arising from the possibility that DM is captured inside the core of a neutron star.…”
Section: Dark Matter Capture In Neutron Starsmentioning
confidence: 99%
“…Note that these models have trouble with neutron star stability [11][12][13]. The conversion of neutrons to dark matter in the neutron star softens the nuclear equation of state to the point that neutron stars above two solar masses are not possible, which is in contradiction with observations.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Fornal and Grinstein [9] have proposed different decay channels involving a dark matter particle. These branches would have been missed by the most precise beta decay method experiments which have detected decay protons [10].Neutron stars have been used to severely constrain these branches [11][12][13] but some models evade these constraints [14]. Czarnecki et al have derived a very general bound of < 0.27 % (95 % C.L.)…”
mentioning
confidence: 99%
“…Neutron stars have been used to severely constrain these branches [11][12][13] but some models evade these constraints [14]. Czarnecki et al have derived a very general bound of < 0.27 % (95 % C.L.)…”
mentioning
confidence: 99%